Contextualisation of the ‘Brickwalls’ of land administration and regulation system affecting the dynamics of formal land market in Nigeria - Akinbola, Kazeem Bolayemi; Md Yassin, Azlina (Open Access Publishing Group, 2017)
The centrality of land to man’s socio-economic and even political survival, has long been recognised as a non-negotiable necessity. Apparently, because of the relative fixity of this resource, coupled with ever soaring demographic bursts, that had made it imperative more than ever before, to ensure the management, administration, control and regulation of its use and development a top priority. However, it must be frankly admitted, that formal land market, which is driven by the dynamics of supply and demand, which are otherwise termed delivery and accessibility respectively, are faced with very unimaginable challenges of unprecedented scales. Although, these ‘brickwalls’ are emanating from very many different contexts, but arguably, the most copious of them are traceable to formal land administration and regulation systems. Therefore, it is in a bid to address this very unfortunate trending turbulence, created and sustained by ‘brickwalls’ of formal land administration and regulation system, as reflected above, that this study was conducted. Hence, subsequent upon literature search that revealed some salient issues, that was evidenced to be brickwalls of land administration and regulation system. Therefore, structured questionnaires were designed with 5point Likert scale format and distributed via purposive and convenience sampling technique, among 450 respondents that were adopted for the sample size, from a sample frame 850 respondents, out of the total sample space of 2408 respondents. It captured relevant officers on permanent and tenured engagement among the various land agencies that jointly constitute the formal land administration and regulation system within the Nigeria’s south-western states of Lagos, Ogun, Oyo, Osun, Ondo and Ekiti, as well as independent land consultants and NGOs with shelter mandate, together with various classes of land users and developers. Sequel to application of AMOS’ version 18 software to conduct Structural Equation Modelling (SEM), the 427 retrieved questionnaires were made through series of integrity tests to establish their reliability and normality. 416 questionnaires were found valid, upon which the analyses were done. The results showed that amongst the three major ‘brickwalls’ studied, human techno-analytical arsenal was found to be of not-so-significant effects on the formal land administration and regulation system and thus resultantly impacts less on the overall supply and demand dynamics of the formal land market. The study recommends among other things, for a very urgent and decisive action to seriously re-align and reconfigure the structure of various constituent units of Nigeria’s land administration and regulation system, so as to engender synergy and collaboration building among them, with a view to making them more optimal in their performance, thus contributing immensely to the operational vibrancy of the formal land market in Nigeria.